Therapeutic itineraries of snakebite victims and antivenom access in southern Mexico. - Chloe Vasquez; Edgar Neri Castro; Eric D Carter (Public Library of Science (PLoS), 2024)
Access to antivenoms in cases of snakebite continues to be an important public health issue around the world, especially in rural areas with poorly developed health care systems. This study aims to evaluate therapeutic itineraries and antivenom accessibility following snakebites in the states of Oaxaca and Chiapas in southern Mexico. Employing an intercultural health approach that seeks to understand and bridge allopathic and traditional medical perceptions and practices, we conducted field interviews with 47 snakebite victims, documenting the therapeutic itineraries of 54 separate snakebite incidents that occurred between 1977 and 2023. Most victims used traditional remedies as a first line of treatment, often to withstand the rigors of a long journey to find antivenoms. The main obstacles to antivenom access were distance, poor antivenom availability, and cost. Standard antivenom treatment is highly valued and sought after, even as traditional beliefs and practices persist within a cultural framework known as the "hot-cold" system. The findings are crucial for informing future enhancements to antivenom distribution systems, health education initiatives, and other interventions aimed at mitigating the impact of snakebites in the region.